Lithium sulfide powder with improved particle size uniformity and sulfide-based solid electrolyte containing the same
Patent Information
- Application Number
- KR1020260034840
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-02-25
- Publication Date
- 2026-09-15
- Estimated Expiration
- 2046-02-25
Smart Images

Figure 112026023323713-PAT00020_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a highly uniform lithium sulfide produced through moisture control and a sulfide-based solid electrolyte comprising the highly uniform lithium sulfide. Background Technology
[0003] Lithium-sulfur secondary batteries have a theoretical energy density of 2,800 Wh / kg (1,675 mAh / g), which is very high compared to currently commercialized lithium secondary batteries. In addition, sulfur-based materials used as cathode active materials are abundant and inexpensive, and are attracting attention as environmentally friendly materials.
[0004] In these lithium-sulfur secondary batteries, the lithium metal used as the negative electrode has a problem in that it grows into a dendrite phase during the charging and discharging process, causing a short circuit inside the battery. Since this degrades battery stability, it is pointed out as a major limitation to the commercialization of lithium-sulfur secondary batteries.
[0005] In addition, to activate sulfur in lithium-sulfur secondary batteries, a composite material must be made with carbon. However, since the sublimation temperature of sulfur is too low (~115℃), ampoules must always be used. Moreover, even when using these ampoules, the degree of adsorption with carbon is very low, so the same process must be repeated several times to obtain an appropriate loading density of sulfur, resulting in high process costs.
[0006] To fundamentally resolve the issues associated with lithium-sulfur secondary batteries, a method using lithium sulfide (Li2S) instead of sulfur as the cathode has been proposed. When lithium sulfide is used as the cathode, it is not necessary to use lithium metal as the anode. Furthermore, due to its high melting temperature (~1000°C), the cathode filling rate can be adjusted to a desired level, allowing for the implementation of the battery through a simpler process. Additionally, various types of post-processing can be performed at high temperatures, which offers the advantage of maximizing the activity of lithium sulfide.
[0007] Meanwhile, unlike conventional lithium-ion batteries using liquid electrolytes, all-solid-state batteries (ASSBs) utilizing solid electrolytes have the advantage of being safer than conventional lithium-ion batteries and capable of operating over a wide range of temperatures, as they eliminate problems such as flammability, corrosion, leakage, and evaporation caused by liquid electrolytes.
[0008] All-solid-state lithium secondary batteries consist of a positive electrode, a negative electrode, and a solid electrolyte. Solid electrolytes are broadly classified into polymer, oxide, and sulfide types. Among these, oxide and sulfide solid electrolytes are being actively researched due to their relatively high ionic conductivity, excellent mechanical properties, and non-flammability.
[0009] Lithium sulfide (Li2S), used as a material for such sulfide-based solid electrolytes, is not produced as a natural mineral and is therefore provided through synthesis.
[0010] One of the conventional synthesis methods for lithium sulfide is a method utilizing the reaction between lithium hydroxide (LiOH) and hydrogen sulfide, a gaseous sulfur source. Japanese Patent Publication No. 09-278423 proposed a method for producing lithium sulfide in a dry manner by pulverizing lithium hydroxide particles to have a diameter of 0.1 to 1.5 mm and heating the reaction between lithium hydroxide and hydrogen sulfide to a temperature of 80 to 445°C under an inert gas atmosphere.
[0011] However, in the above-described dry lithium sulfide manufacturing method, lithium hydroxide is highly hygroscopic and prone to aggregation, making it difficult to handle in large quantities. Furthermore, it is difficult to achieve fine pulverization of the obtained lithium sulfide, and there is a problem that mass production of lithium sulfide is difficult. Prior art literature
[0013] Japanese Patent Publication No. JP 09-278423 (October 28, 1997) The problem to be solved
[0014] The present invention aims to provide lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide and an organic solvent with hydrogen sulfide gas, and a raw material for manufacturing a sulfide-based solid electrolyte containing the same. means of solving the problem
[0015] The present invention is a lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide (LiOH) and an organic solvent with hydrogen sulfide (H2S) gas, wherein the lithium sulfide powder is a lithium sulfide powder satisfying the following relationship 1.
[0016] [Relationship 1]
[0017] ≤ 120
[0018] (In relation 1, , and These are particle sizes (㎛) corresponding to 10%, 50%, and 90% of the maximum value in the lithium sulfide particle size distribution, respectively, and is the average value (㎛) of the particle size distribution of lithium sulfide, am.)
[0019] In the lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide and an organic solvent of the present invention with hydrogen sulfide gas, the concentration of lithium hydroxide in the reaction solution may be 0.1 to 10 M.
[0020] In the lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide and an organic solvent of the present invention with hydrogen sulfide gas, the organic solvent may include an amide-based organic solvent and a sulfur-containing organic solvent.
[0021] In the lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide and an organic solvent of the present invention with hydrogen sulfide gas, the volume ratio of the organic solvent to the sulfur-containing organic solvent may be 1:0.01 to 1.
[0022] In the lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide and an organic solvent of the present invention with hydrogen sulfide gas, the amide-based organic solvent may be one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), N,N´-dimethylacetamide (DMAc), hexamethylphosphamide (HMPA), and N,N-dimethylformamide (DMF).
[0023] In the lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide and an organic solvent of the present invention with hydrogen sulfide gas, the sulfur-containing organic solvent may be one or more selected from the group consisting of dimethyl sulfone, methyl ethyl sulfone, diethyl sulfone, and tetramethylene sulfone.
[0024] The present invention can provide a raw material for manufacturing a sulfide-based solid electrolyte comprising lithium sulfide powder according to the present invention, a sulfur compound other than lithium sulfide, and a lithium halide.
[0025] In the raw material for manufacturing the sulfide-based solid electrolyte of the present invention, the sulfur compound may be one or more selected from the group consisting of phosphorus sulfide, silicon sulfide, boron sulfide, and germanium sulfide.
[0026] In the raw material for manufacturing the sulfide-based solid electrolyte of the present invention, the lithium halide may be one or more selected from the group consisting of lithium chloride, lithium bromide, and lithium iodide.
[0027] In the raw material for manufacturing the sulfide-based solid electrolyte of the present invention, the weight ratio of lithium sulfide ultrafine powder : sulfur compound : lithium halide may be 1 : 1 to 20 : 0.1 to 10. Effects of the invention
[0028] The present invention can provide lithium sulfide with fine and uniformly distributed particles by immediately removing moisture so that particles do not easily aggregate during the lithium sulfide synthesis process, and the lithium sulfide powder of the present invention can be used as a raw material capable of providing a solid electrolyte with high ion conductivity and low resistance. Brief explanation of the drawing
[0030] Figure 1 is a graph of the particle size analysis results of lithium hydroxide and lithium sulfide prepared according to Example 1, Comparative Example 1, and Comparative Example 2. Figure 2 is a graph of the particle size analysis results of lithium hydroxide and lithium sulfide prepared according to Examples 1, 2, and 3. Specific details for implementing the invention
[0031] The lithium sulfide powder of the present invention and the raw material for manufacturing a sulfide-based solid electrolyte containing the lithium sulfide powder are described in detail below. The drawings introduced in the specific description for implementing the invention are provided as examples to ensure that the concept of the present invention is sufficiently conveyed to those skilled in the art. Accordingly, the present invention is not limited to the drawings presented below and may be embodied in other forms, and the drawings presented below may be exaggerated to clarify the concept of the present invention. Unless otherwise defined, technical and scientific terms used herewith have the meanings commonly understood by those skilled in the art to which this invention pertains, and descriptions of known functions and configurations that could unnecessarily obscure the essence of the present invention are omitted in the following description and attached drawings.
[0033] The present invention relates to lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide (LiOH) and an organic solvent with hydrogen sulfide (H2S) gas, and to a raw material for manufacturing a sulfide-based solid electrolyte containing the same.
[0034] The lithium sulfide powder of the present invention is a lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide (LiOH) and an organic solvent with hydrogen sulfide (H2S) gas, and is a lithium sulfide powder satisfying the following equation 1.
[0035] [Relationship 1]
[0036] ≤ 120
[0037] (In the above relationship 1, , and ε₀, 50%, and 90% of the maximum value in the lithium sulfide particle size distribution, respectively, are particle sizes (μm), and μ is the average value (μm) of the lithium sulfide particle size distribution, am.)
[0038] Equation 1 for the lithium sulfide powder of the present invention is the standard deviation (σ) of lithium sulfide, and the smaller the standard deviation value, the more uniform the size may be; as a specific example, the standard deviation (σ) may be 100 to 120, more specifically 110 to 118, and preferably 110 to 117. In Equation 1, D 10 , D 50 and D 90 ≡ represents the particle size (μm) corresponding to the points where the cumulative volume of the cumulative particle size distribution based on particle size distribution measurement reaches 10%, 50%, and 90%, respectively, and μ is the average value (μm) of the particle size distribution of lithium sulfide, It can be derived as, and D 10 , D 50 and D 90 From the measurement results, it is possible to provide lithium sulfide powder with high uniformity satisfying Equation 1.
[0039] According to the present invention, the uniformity of the precisely controlled lithium sulfide powder can significantly improve the ion conductivity of the sulfide-based solid electrolyte using the lithium sulfide powder, and the lithium sulfide powder satisfying the above relationship 1 has particularly excellent uniformity and can be used as a main raw material for manufacturing a solid electrolyte with high ion conductivity.
[0040] The lithium sulfide powder of the present invention is a lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide (LiOH) and an organic solvent with hydrogen sulfide (H2S) gas, wherein the concentration of lithium hydroxide in the reaction solution may be 0.1 to 10 M, more preferably 1 to 5 M, and when within this range, lithium hydroxide and hydrogen sulfide react well to synthesize the desired lithium sulfide.
[0041] The lithium sulfide powder of the present invention is a lithium sulfide powder formed by the reaction of a reaction solution containing lithium hydroxide (LiOH) and an organic solvent with hydrogen sulfide (H2S) gas, wherein the organic solvent may include an amide-based organic solvent and a sulfur-containing organic solvent. The volume ratio of the amide-based organic solvent to the sulfur-containing organic solvent in the organic solvent may be 1:0.01 to 1, and the amide-based organic solvent may be one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), N,N´-dimethylacetamide (DMAc), hexamethylphosphamide (HMPA), and N,N-dimethylformamide (DMF), and the sulfur-containing organic solvent may be one or more selected from the group consisting of dimethylsulfone, methylethylsulfone, diethylsulfone, and tetramethylenesulfone.
[0042] The present invention can provide a raw material for manufacturing a sulfide-based solid electrolyte comprising the lithium sulfide powder of the present invention, a sulfur compound other than lithium sulfide, and a lithium halide.
[0043] In the raw material for manufacturing a sulfide-based solid electrolyte of the present invention, the sulfur compound may be one or more selected from the group consisting of phosphorus sulfide, silicon sulfide, boron sulfide, and germanium sulfide, and the lithium halide may be one or more selected from the group consisting of lithium chloride, lithium bromide, and lithium iodide, and the weight ratio of lithium sulfide powder : sulfur compound : lithium halide may be 1 : 1 to 20 : 0.1 to 10.
[0044] The lithium sulfide powder according to the present invention has the advantage of being able to produce fine and uniformly distributed lithium sulfide and to produce it in large quantities by immediately removing moisture during the synthesis process and preventing particles from easily aggregating by reacting a reaction solution containing lithium hydroxide (LiOH) and an organic solvent with hydrogen sulfide in a high-temperature and high-pressure environment through a wet process.
[0045] One embodiment for manufacturing lithium sulfide powder according to the present invention may be a method for manufacturing lithium sulfide comprising: a) a step of raising a reaction solution containing lithium hydroxide (LiOH) and an organic solvent to 150°C or higher and then injecting hydrogen sulfide (H2S) gas to react; and b) a step of repeating the process of injecting hydrogen sulfide (H2S) gas into the reaction solution and re-reacting it one or more times when the internal pressure of the reactor is lowered to 1 to 2 atmospheres after step a).
[0046] The lithium sulfide powder of the present invention and the method for manufacturing a raw material for a sulfide-based solid electrolyte containing lithium sulfide according to the present invention will be described in detail below.
[0047] First, a) a step of raising the temperature of a reaction solution containing lithium hydroxide (LiOH) and an organic solvent to 150°C or higher, and then injecting hydrogen sulfide (H2S) gas to react; can be performed.
[0048] In one example of the present invention, the reaction solution is prepared by dissolving lithium hydroxide in an organic solvent, and as a specific example, the organic solvent may include an amide-based organic solvent and a sulfur-containing organic solvent. Thus, by using a mixed organic solvent in which an amide-based organic solvent and a sulfur-containing organic solvent are mixed, the reaction between lithium hydroxide and hydrogen sulfide is further activated, allowing lithium sulfide to be synthesized effectively and its purity to be further improved.
[0049] As a specific example, the above amide-based organic solvent may be one or more selected from the group consisting of N-methyl-2-pyrrolidone (NMP), N,N´-dimethylacetamide (DMAc), hexamethylphosphamide (HMPA), and N,N-dimethylformamide (DMF), and preferably may be N-methyl-2-pyrrolidone (NMP). The above sulfur-containing organic solvent may be a sulfone-based solvent, and specifically, for example, may be one or more selected from the group consisting of dimethylsulfone, methylethylsulfone, diethylsulfone, and tetramethylenesulfone.
[0050] In addition, as mentioned above, when a mixed organic solvent comprising an amide-based organic solvent and a sulfur-containing organic solvent is used as a reaction solvent, the reaction between lithium hydroxide and hydrogen sulfide is further activated, allowing for the effective synthesis of lithium sulfide and further improvement in purity. Therefore, it is desirable to use a mixed organic solvent comprising an amide-based organic solvent and a sulfur-containing organic solvent as a reaction solvent.
[0051] As a specific example, the volume ratio of the amide-based organic solvent to the sulfur-containing organic solvent in the above-mentioned mixed organic solvent may be 1:0.01 to 1, more preferably 1:0.05 to 0.4, and even more preferably 1:0.07 to 0.2. The reaction activation effect is excellent within this range.
[0052] In addition, in one example of the present invention, step a) may be performed at a reaction temperature of 150°C or higher, more preferably at a reaction temperature of 180 to 250°C, even more preferably at 185 to 240°C, and even more preferably at 190 to 220°C. When a wet process is performed at such high temperatures, lithium hydroxide and hydrogen sulfide react more effectively, so that lithium sulfide can be synthesized more effectively.
[0053] Next, b) after step a), when the internal pressure of the reactor is lowered to 1 to 2 atmospheres, the process of injecting hydrogen sulfide (H2S) gas into the reaction solution again and re-reacting it can be repeated one or more times.
[0054] That is, when the hydrogen sulfide gas injected in step a) is used for the synthesis of lithium sulfide and the internal pressure of the reactor is lowered to 1 to 2 atmospheres, preferably 1.5 to 2 atmospheres, the process of injecting hydrogen sulfide (H2S) gas and re-reacting can be repeated one or more times, preferably 10 to 100 times, and more preferably 30 to 50 times. By repeating the process of injecting hydrogen sulfide gas and re-reacting several times in this way, most of the lithium hydroxide can be converted into lithium sulfide.
[0055] In this way, when the lithium sulfide synthesis reaction is performed in a high-temperature and high-pressure environment, moisture is immediately removed so that particles do not easily aggregate, thereby providing fine and uniformly distributed lithium sulfide.
[0056] In addition, when hydrogen sulfide (H2S) gas is injected in steps a) and b), an inert gas may be injected together, and the volume ratio of hydrogen sulfide (H2S) gas to inert gas may be 10:90 to 99:1, more preferably 25:75 to 90:10, and even more preferably 40:60 to 80:20. As the volume of hydrogen sulfide (H2S) gas increases, the reaction rate improves, and if there is too much argon, the reaction rate decreases, causing particles to clump together and potentially lowering the yield.
[0057] Furthermore, a method for producing lithium sulfide according to an example of the present invention may further include: c) a step of obtaining a primary reaction product by removing the mixed organic solvent of the reaction solution after step b); d) a step of raising the temperature of the primary reaction product to 100°C or higher and then injecting hydrogen sulfide (H2S) gas to carry out a dry reaction under a pressure higher than atmospheric pressure; and e) a step of removing water, which is a reaction byproduct, through a vacuum pump after step d), and then injecting hydrogen sulfide (H2S) gas again and carrying out a dry re-reaction, repeating the process one or more times.
[0058] Step c) above is a step of obtaining a primary reaction product by removing the organic solvent after the wet reaction of lithium sulfide in step b). The method of removing the organic solvent is not particularly limited, and for example, the organic solvent can be removed through an evaporative drying method.
[0059] Subsequently, a dry process may be additionally performed to completely convert the unreacted lithium hydroxide remaining in small amounts in the primary reactant into lithium sulfide. Specifically, the steps include: d) raising the temperature of the primary reactant to 100°C or higher and then injecting hydrogen sulfide (H2S) gas to react under a pressure higher than atmospheric pressure; and e) removing water, which is a reaction byproduct, through a vacuum pump after step d), and then injecting hydrogen sulfide (H2S) gas again and repeating the reaction process one or more times.
[0060] At this time, steps d) and e) can be performed independently of each other at a reaction temperature of 100 to 150°C, and more preferably at a reaction temperature of 120 to 140°C. In this range, unreacted lithium hydroxide and hydrogen sulfide react well to obtain high-purity lithium sulfide.
[0061] In addition, in one example of the present invention, steps d) and e) may further inject an inert gas along with hydrogen sulfide (H2S) gas. At this time, the inert gas may be one or more selected from the group consisting of argon (Ar), helium (He), and nitrogen (N2).
[0062] In addition, the volume ratio of the hydrogen sulfide (H2S) gas to the inert gas may be 1:0.1 to 10, and more preferably, the volume ratio of the hydrogen sulfide (H2S) gas to the inert gas may be 1:0.5 to 3. Within this range, unreacted lithium hydroxide and hydrogen sulfide react well to obtain high-purity lithium sulfide.
[0063] Meanwhile, after the process of injecting hydrogen sulfide gas and re-reacting, a process to remove water generated as a reaction byproduct must be performed; if the water is not removed, unreacted lithium hydroxide may remain as an impurity. In this case, there are no specific restrictions on the method of water removal, and it can be removed, for example, using a vacuum pump.
[0064] Step e) above can be repeated until no moisture forms when observed through a sight glass, and it is preferable to obtain the lithium sulfide in a glove box after the reaction is complete.
[0065] In this way, by performing the dry processes of steps d) to e) after the wet processes of steps a) to c), the fine and uniformly distributed lithium sulfide intended in the present invention can be produced in large quantities.
[0066] In addition, another aspect of the present invention relates to a method for manufacturing a sulfide-based solid electrolyte using lithium sulfide produced by the aforementioned manufacturing method, and more specifically, to a method for manufacturing a sulfide-based solid electrolyte comprising: A) a step of producing lithium sulfide ultrafine powder by first ball milling the previously produced lithium sulfide powder; B) a step of synthesizing an electrolyte precursor by second ball milling a composition comprising the lithium sulfide ultrafine powder, a sulfur compound (excluding lithium sulfide), and a lithium halide; and C) a step of producing a sulfide-based solid electrolyte by heat-treating the electrolyte precursor. The first ball milling may utilize two or more types of zirconia balls with different particle sizes, but is not limited thereto.
[0067] Thus, the method for manufacturing a sulfide-based solid electrolyte according to the present invention can produce lithium sulfide having a fine and uniform size. Through this, a solid electrolyte with excellent ion conductivity characteristics can be provided, and there is an advantage that a sulfide-based solid electrolyte with excellent ion conductivity characteristics can be easily manufactured by first ball-milling the lithium sulfide raw material powder to produce lithium sulfide ultrafine powder with an average particle size of 20 μm or less, and then mixing it with a sulfur compound and a lithium halide to produce a solid electrolyte.
[0068] First, A) a step of producing lithium sulfide ultrafine powder by first ball milling of lithium sulfide powder can be performed. As a more specific example, the zirconia balls used in the first ball milling may have a particle size of 0.5 to 5 mm, and when using different zirconia balls, they may include a second zirconia ball with a particle size of 6 to 15 mm together with the first zirconia ball, and more preferably, they may include a first zirconia ball with a particle size of 1 to 5 mm and a second zirconia ball with a particle size of 8 to 12 mm.
[0069] At this time, the first ball milling can be performed at a rotational speed of 200 to 1000 rpm, more preferably at 250 to 900 rpm, even more preferably at 300 to 800 rpm, and even more preferably at 400 to 600 rpm. In addition, the stirring time can be performed for 1 to 120 minutes, more preferably at 10 to 90 minutes, and even more preferably at 15 to 60 minutes. Within this range, lithium sulfide ultrafine powder with an average particle size of 20 μm or less can be effectively produced even with a shorter stirring time.
[0070] Such first ball milling can be performed using any ball mill commonly used in the industry without special limitation, and specifically, for example, the ball milling can be performed using an electric ball mill, a stirred ball mill, or a planetary ball mill.
[0071] Meanwhile, during the first ball milling, the zirconia ball to lithium sulfide powder may be mixed in a weight ratio of 1 to 10 to 1, more preferably 1.5 to 8 to 1, and even more preferably 2 to 5 to 1. Ball milling can be performed smoothly within such a range.
[0072] In addition, the first ball milling can be performed under an inert gas atmosphere, for example, under an atmosphere of nitrogen, argon, helium, or a mixture thereof, and as a more specific example, it can be performed in a glove box under an inert gas atmosphere. Since lithium sulfide has high hygroscopicity and is prone to aggregation, if ball milling is not performed under an inert gas atmosphere, the lithium sulfide may actually aggregate.
[0073] Meanwhile, the average particle size of the lithium sulfide powder synthesized through a dry or wet process prior to the first ball milling may be 100 μm or more, and when the lithium sulfide ultrafine powder is ball milled according to the conditions described above, the average particle size may be 20 μm or less, more preferably 1 to 15 μm, and even more preferably 1 to 10 μm. When manufacturing a sulfide-based solid electrolyte using lithium sulfide ultrafine powder with an average particle size of 20 μm or less, superior ionic conductivity and resistance characteristics can be secured.
[0074] Next, B) a step of synthesizing an electrolyte precursor by ball-milling a composition comprising the above-mentioned lithium sulfide ultrafine powder, a sulfur compound (excluding lithium sulfide), and a lithium halide can be performed.
[0075] In one example of the present invention, the sulfur compound may be used without special limitation as long as it is commonly used in the art, and specifically, for example, may be one or more selected from the group consisting of phosphorus sulfide, silicon sulfide, boron sulfide, and germanium sulfide.
[0076] In one example of the present invention, the lithium halide may be used without special limitation as long as it is commonly used in the art, and specifically, it may be one or more selected from the group consisting of lithium chloride, lithium bromide and lithium iodide.
[0077] At this time, the weight ratio of the lithium sulfide ultrafine powder : sulfur compound : lithium halide may be 1 : 1 to 20 : 0.1 to 10, more preferably 1 : 5 to 15 : 1 to 5, even more preferably 1 : 7 to 13 : 1.5 to 4, and even more preferably 1 : 8 to 12 : 2 to 3. Superior ion conductivity and resistance characteristics can be secured within such a range.
[0078] Meanwhile, the second ball milling can be performed using zirconia balls with a particle size of 0.5 to 10 mm, and, of course, can also be performed using two or more types of zirconia balls with different particle sizes, similar to the first ball milling. As a more specific example, the zirconia balls used in the second ball milling may include a first zirconia ball with a particle size of 0.5 to 5 mm and a second zirconia ball with a particle size of 6 to 15 mm, and more preferably, may include a first zirconia ball with a particle size of 1 to 5 mm and a second zirconia ball with a particle size of 8 to 12 mm.
[0079] In addition, the second ball milling can be performed at a rotational speed of 200 to 1500 rpm, more preferably at 250 to 1200 rpm, even more preferably at 300 to 1000 rpm, and even more preferably at 400 to 800 rpm. In addition, the stirring time can be performed for 1 to 60 hours, more preferably at 10 to 50 hours, and even more preferably at 15 to 30 hours. A uniformly mixed electrolyte precursor can be synthesized within such a range.
[0080] The above second ball milling can also be performed using any ball mill commonly used in the industry without special limitation, and specifically, for example, the ball milling can be performed using an electric ball mill, a stirred ball mill, or a planetary ball mill.
[0081] Meanwhile, during the second ball milling, the zirconia ball:composition may be incorporated in a weight ratio of 1 to 20:1, more preferably in a weight ratio of 3 to 15:1, and even more preferably in a weight ratio of 5 to 10:1. Ball milling can be performed smoothly within such a range.
[0082] In addition, the second ball milling can also be performed under an inert gas atmosphere, for example, under an atmosphere of nitrogen, argon, helium, or a mixture thereof, and as a more specific example, can be performed in a glove box under an inert gas atmosphere.
[0083] Next, step C) of heat-treating the electrolyte precursor to produce a sulfide-based solid electrolyte may be performed; as a specific example, the heat treatment may be performed at a temperature of 400 to 800°C for 1 to 10 hours, more preferably at a temperature of 450 to 700°C for 2 to 8 hours, and even more preferably at a temperature of 500 to 600°C for 3 to 5 hours. A sulfide-based solid electrolyte with excellent ionic conductivity can be effectively produced within such a range.
[0084] Subsequently, if necessary, a step of forming the above sulfide-based solid electrolyte into an electrolyte membrane using a cell jig or the like may be further performed.
[0086] Hereinafter, the method for manufacturing highly uniform lithium sulfide through moisture control and the method for manufacturing a sulfide-based solid electrolyte according to the present invention will be described in more detail through examples. However, the following examples are merely references for explaining the present invention in detail, and the present invention is not limited thereto and can be implemented in various forms.
[0087] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as generally understood by one of the art to which the present invention pertains. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention. Additionally, units of additives not specifically stated in the specification may be in weight percent.
[0089] 1) Lithium sulfide (Li 2 S) Manufacturing
[0090] [Example 1]
[0091] 450 ml of N-methyl-2-pyrrolidone (NMP), 50 ml of tetramethylenesulfone, and 25 g of lithium hydroxide (LiOH) were added to a 2 L reactor, and the temperature was raised to 200°C. When the temperature reached 200°C, 2 L of hydrogen sulfide (H2S) and 2 L of argon (Ar) were injected into the reactor, and 1 L of H2S and 1 L of argon (Ar) were additionally injected while stirring at 50 rpm. Stirring continued until the pressure increased by the over-injected H2S reached 1.5 atm, and then the process of additionally injecting 1 L of H2S and 1 L of argon (Ar) was repeated 40 times.
[0092] Subsequently, the mixed solvent was removed and the primary reaction product was obtained by drying using an evaporative drying method. Then, to remove unreacted LiOH from the dried primary reaction product, the primary reaction product was added to a 2 L reactor, and 5 L of argon (Ar) and 7 L of H2S were injected while stirring at 50 rpm at 130°C. After the injection, the reaction was carried out for 1 minute, and the reaction byproducts, water and remaining gas, were removed by vacuum. This process was repeated until no moisture condensed when observed through a sight glass, and after the reaction was completed, lithium sulfide powder was obtained from a glove box.
[0093] The particle size distribution of the prepared lithium sulfide powder was measured using a laser diffraction particle size analyzer, and the results are shown in Figure 1 and [Table 1] below. In addition, based on the measured particle size distribution, the standard deviation (σ) value was calculated according to the aforementioned relationship 1, and the results are shown in [Table 1] below.
[0095] [Examples 2 and 3]
[0096] All processes were carried out in the same manner as in Example 1, except that lithium sulfide powder was prepared by adjusting the volume ratio of hydrogen sulfide (H2S) and argon (Ar) differently as described in [Table 1] below.
[0098] [Comparative Examples 1 and 2]
[0099] All processes were carried out in the same manner as in Example 1, except that lithium sulfide powder was prepared by adjusting the reaction temperature and pressure differently as described in [Table 1] below.
[0101] Reaction pressure (atmospheric pressure) Reaction temperature (°C) Gas volume ratio H2S:Ar Particle size distribution (㎛) D 10 D 50 D 90 lithium hydroxide - - - 43 142 342 124.32 Comparative Example 1 1 150 50:50 42 135 338 123.58 Example 1 1.5 200 50:50 37 125 315 116.00 Example 2 1.5 200 25:75 51 144 350 116.01 Example 3 1.5 200 75:25 35 119 308 117.33 Comparative Example 2 0.5 100 50:50 49 146 356 128.11
[0102] Referring to [Table 1] above, it can be seen that lithium sulfide produced under high temperature and high pressure conditions has fewer particles and is more uniform than lithium hydroxide or Comparative Examples 1 and 2.
[0103] In addition, as the ratio of hydrogen sulfide (H2S) gas to argon increased, the reaction rate became faster, and when the ratio of hydrogen sulfide (H2S):argon was 25:75, the reaction rate was slow, resulting in a loss of yield due to particle clumping.
[0105] 2) Preparation of solid electrolytes
[0106] In a glove box under a nitrogen atmosphere, 4.59 g of the lithium sulfide powder prepared above, 4.44 g of phosphorus pentasulfide (P2S5), 1.7 g of lithium chloride (LiCl), and 85.84 g of zirconia balls (particle size 3 mm) were placed into a crucible, and then the crucible cap was closed and sealed.
[0107] Afterward, ball milling was performed under conditions of a rotation speed of 550 rpm and a stirring time of 24 hours (ball mill equipment: PULVERISETTE 6 Planetary Mono Mill, manufacturer: FRITSCH), and then heat treatment was performed at 550℃ for 3 hours.
[0108] Next, an electrolyte membrane was prepared using a cell jig with the heat-treated sample, and the ionic conductivity was measured using an impedance meter, and the results are shown in [Table 2] below.
[0110] Resistance (R, ohm) Pellet thickness (cm) Ionic conductivity (S / cm) Comparative Example 1 124 0.194 1.98 × 10 -3 Example 1 88 0.192 2.80 × 10 -3 Comparative Example 2 154 0.193 1.58 × 10 -3
[0111] Referring to [Table 2] above, it can be confirmed that the ion conductivity characteristics of Example 1, which is manufactured in a high-pressure and high-temperature environment and has finer and more uniform particle size, are particularly excellent. Specifically, the ion conductivity characteristics of Example 1 were improved by about 1.41 times compared to Comparative Example 1 and by about 1.77 times compared to Comparative Example 2.
[0112] Although the present invention has been described above through specific details and limited embodiments, this is provided merely to aid in a more comprehensive understanding of the invention, and the invention is not limited to the above embodiments. Those skilled in the art can make various modifications and variations from this description.
[0113] Accordingly, the scope of the present invention is not limited to the described embodiments, and all things equivalent to or having equivalent variations to the claims set forth below, as well as the claims set forth below, shall be considered to fall within the scope of the concept of the present invention.
Claims
Claim 1 A lithium sulfide powder formed by the reaction of a reaction solution comprising lithium hydroxide (LiOH), a sulfone-based organic solvent, and an amide-based organic solvent with hydrogen sulfide (H2S) gas, wherein the lithium sulfide powder satisfies the following Equation 1. [Equation 1] ≤ 120(in the above relationship 1, , and These are particle sizes (㎛) corresponding to 10%, 50%, and 90% of the maximum value in the lithium sulfide particle size distribution, respectively, and is the average value (㎛) of the particle size distribution of lithium sulfide, am.) Claim 2 Lithium sulfide powder according to claim 1, wherein the concentration of lithium hydroxide in the reaction solution is 0.1 to 10 M. Claim 3 delete Claim 4 In claim 1, the organic solvent is a lithium sulfide powder having a volume ratio of amide-based organic solvent to sulfone-based organic solvent of 1:0.01 to 1. Claim 5 In claim 1, the lithium sulfide powder is one or more of the amide-based organic solvents selected from the group consisting of N-methyl-2-pyrrolidone (NMP), N,N´-dimethylacetamide (DMAc), hexamethylphosphamide (HMPA), and N,N-dimethylformamide (DMF). Claim 6 In claim 1, the sulfone-based organic solvent is one or more selected from the group consisting of dimethyl sulfone, methyl ethyl sulfone, diethyl sulfone, and tetramethylene sulfone, and is a lithium sulfide powder. Claim 7 A raw material for manufacturing a sulfide-based solid electrolyte comprising lithium sulfide powder according to any one of claims 1, 2, and 4 through 6, a sulfur compound other than lithium sulfide, and a lithium halide. Claim 8 In claim 7, the above sulfur compound is a raw material for manufacturing a sulfide-based solid electrolyte, wherein the sulfur compound is one or more selected from the group consisting of phosphorus sulfide, silicon sulfide, boron sulfide, and germanium sulfide. Claim 9 In claim 7, the lithium halide is a raw material for manufacturing a sulfide-based solid electrolyte, wherein the lithium halide is one or more selected from the group consisting of lithium chloride, lithium bromide, and lithium iodide. Claim 10 In claim 7, the raw material for manufacturing a sulfide-based solid electrolyte, wherein the weight ratio of the lithium sulfide powder : sulfur compound : lithium halide is 1 : 1 to 20 : 0.1 to 10.
Citation Information
Patent Citations
A preparation method and application of lithium sulfide
CN119735171A
Manufacturing method of high purity lithium sulfide using mixed organic solvent
KR102562588B1
